Interação entre a política fiscal e monetária: uma análise sobre o regime de dominância vigente na economia brasileira. - Nobrega, Wellington Charles Lacerda (2016)
This research aims to investigate the dominance regime (monetary or fiscal) prevailing in Brazilian economy in the period from 2003 to 2015. For this, an autoregressive vectors model (VAR) was used as first approach. The results of this step suggest the existence of a monetary dominance relationship, as described by Sargent and Wallace (1981) and Blanchard (2004). However, a structural change in the relationship between variables was verified. And, through multiple regressions of debt equation with the inclusion of dummy variables, was found that the money supply began to show negative relationship with public debt, suggesting that the expansion of the monetary base was used to stabilize public accounts. This results suggests that there is evidence of a fiscal dominance regime for the recent period. Fact borne out by the Markov-Switching autoregressive vectors model (MS-VAR), where it identified the existence of two clearly defined regimes in the analyzed period.